Therapeutic effects of the transplantation of VEGF overexpressing bone marrow mesenchymal stem cells in the hippocampus of murine model of Alzheimer’s disease - Garcia, Karina d.; Ornellas, Felipe L.; Matsumoto, Priscila; Patti, Camilla d.; Mello, Luiz E.; Frussa-Filho, Roberto; Han, Sang W.; Longo, Beatriz M. (Frontiers in Aging Neuroscience, 2014)
Alzheimer´s disease (AD) is clinically characterized by progressive memory loss, behavioural and learning dysfunction and cognitive deficits, such as alterations in social interactions. The major pathological features of AD are the formation of senile plaques and neuroﬁbrillary tangles together with neuronal and vascular damage. The double transgenic mouse model of AD (2xTg-AD) with the APPswe/PS1dE9 mutations shows characteristics that are similar to those observed in AD patients, including social memory impairment, senile plaque formation and vascular deﬁcits. Mesenchymal stem cells (MSCs), when transplanted into the brain, produce positive effects by reducing Aβ deposition in transgenic APP/PS1 mice. Vascular endothelial growth factor (VEGF), exhibits neuroprotective effects against the excitotoxicity implicated in the AD neurodegeneration. The present study investigates the effects of MSCs overexpressing VEGF in hippocampal neovascularization, cognitive dysfunction and senile plaques present in 2xTg-AD transgenic mice. MSC were transfected with uP-VEGF vector, by electroporation and expanded at the 14th passage. 2xTg-AD animals at 6, 9 and 12 months old were transplanted with MSC-VEGF or MSC. The animals were tested for behavioral tasks to access locomotion, novelty exploration, learning and memory, and their brains were analyzed by IHC for vascularization and Aβ plaques. MSC-VEGF treatment favored the neovascularization and diminished senile plaques in hippocampal specific layers. Consequently, the treatment was able to provide behavioral benefits and reduce cognitive deficits by recovering the innate interest to novelty and counteracting memory deficits present in these AD transgenic animals. Therefore, this study has important therapeutic implications for the vascular damage in the neurodegeneration promoted by Alzheimer’s disease.